OPTIMALISASI STRUKTUR ORGANISASI INDUSTRI KREATIF MELALUI TEORI ORGANISASI MODERN: IMPLEMENTASI DALAM PROGRAM PENGABDIAN MASYARAKAT - Adelia Dwi Sagita; Alfina Damayanti; Andini Andini; Hamzah Abdul Falah Sapjan; Meiry Hana Wijaya (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Inefficient organizational structures remain a major challenge for the development of local creative industries. This study aims to optimize the organizational structure of creative industry communities by applying modern organizational theory within a community service framework. The research employs participatory action research with direct interventions such as training, structural mapping, and the development of adaptive work systems. The results indicate a significant improvement in coordination efficiency, productivity, and program sustainability. Social impacts include increased public trust, active member participation, and enhanced community capacity to build strategic partnerships. These findings highlight the importance of integrating modern organizational approaches in revitalizing creative institutional communities.